SECUNDUM ATRIAL SEPTAL DEFECTS COMPLICATED WITH SEVERE PULMONARY HYPERTENSION IN PREGNANCY: MANAGEMENT AND OUTCOME (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Background: Atrial septal defects (ASD) are the third most common type of congenital heart disease, that allows shunting of blood between the systemic and the pulmonary circulations. ASD complicated with severe pulmonary hypertension (PH) often occurs in median age, and pregnancy should be prevented since this will contributed to both high maternal mortality, and complication in pregnancy. Objective: To discuss management and outcomes of secundum atrial septal defects complicated with severe pulmonary hypertension in pregnancy. Case: A 21-year-old woman, G2P1AO, referred to Maternal Fetal Medicine Division on March 30, 2017 with 31 weeks of pregnancy and shortness of breathing. Further investigation revealed that she had history of atrial septal defects that was diagnosed 2 years before admission. Ultrasound examination was performed with conclusion 31 weeks intrauterine pregnancy with intrauterine growth restriction (IUGR). Echocardiography result indicated large secundum ASD, severe PH, severe tricuspid regurgitation (TR), severe pulmonary regurgitation (PR), and ejection fraction (EF) 43%. After closed discussion with the patient and family, the team decided to perform C-section after lung maturation. On April 10, 2017 patient underwent C-section under epidural analgesia with the pregnancy results female baby, 1170 g, APGAR Score 7/8. The patient treated in ICCU for 3 days and went home after 7 days of treatment. Conclusion: Large secundum ASD complicated with severe PH in pregnancy should be carefully managed. Pregnancy termination should be considered, particulary if the disease threatened the mother and caused IUGR in pregnancy. Keywords: Pregnancy, ASD, PH, management.